Managing TikTok Content Strategies to Enhance Tourist Engagement: A Case Study of Bukit Sinyonya Tourism Village - Fadhilah; Lusianingrum, Farah Putri Wenang; Saputra, Galih Ginanjar (Journal of Tourism Sustainability, 2025)
This study explores strategic approaches to managing TikTok content to enhance tourist attraction at the Bukit Sinyonya Tourism Village in Banten. Using a qualitative case study method, the research examines how the local tourism awareness group (Pokdarwis) organises content planning, creative production, and distribution on TikTok. Data were gathered through in-depth interviews, participant observation, and digital content analysis. Drawing on content marketing theory and narrative engagement theory, the study identifies three key stages in content strategy: crafting emotionally resonant themes, producing authentic short videos, and evaluating audience interaction using TikTok analytics. Visual aesthetics, emotional storytelling, and trend adaptation significantly influence audience engagement and visit intention. The findings contribute theoretically by contextualising community-based digital marketing within rural tourism promotion, and practically by offering actionable strategies for local tourism managers. This research highlights how authentic, experience-driven storytelling on social media can strengthen destination branding and foster sustainable tourism development in digitally emerging communities.